Prevenzione primaria della malattia cardiovascolare: c'è bisogno di un'aspirina? - Fulvio Floccari; Fulvio Marrocco; Rodolfo Rivera; Luca Di Lullo (AboutScience Srl, 2019)
The efficacy of antiplatelet treatment with aspirin in the primary prevention of major cardiovascular events was questioned during 2018, following a new series of trials that we summarize here in a quick synoptic overview. The three studies involved are the ASPREE trial, the ASCEND study and the ARRIVE trial. These studies all have a double-blind randomized design, and 100 mg/day aspirin was administered with an intention-to-treat approach and against placebo. Age of the enrolled patients, prevalence of diabetes mellitus and geographical location of other studies are just some of the elements analyzed here, in addition to the different problems of cardiovascular events. The ASPREE study observed a marginal reduction of cardiovascular events with the use of aspirin, by approximately 5% with a confidence interval at risk of insignificancy. On the other hand, the increased risk of a hemorrhagic event appeared to be rather robust, resulting between 18% and 62%. The ASCEND study observed a reduction in cardiovascular events of around 12%, offset by an increase in the risk of major bleeding between 9% and 52%. The ARRIVE study did not detect any incidence of major cardiovascular events, while the risk of major bleeding appeared to even double. The evidences of the current literature push us to review a widespread conviction among professionals who fight the war against cardiovascular disease every day: the prescription of aspirin in the primary prevention can no longer happen systematically, and every single prescription need care between benefits and dangers connected to the treatment. (Cardionephrology)